Application of the Environmental Based Inquiry Learning Model to Improve Solution Ability Problems and Student Learning Outcomes about Science Class IV SDN Inpres Kabonena - Arham, Arham; Suherman, Suherman; Jamhari, Mohammad (Universitas Tadulako, 2018)
This study aims to improve the students' abilities through the application of an environmentally-based guided inquiry learning model in grade IV SDN INPRES Kabonena and the student learning outcomes in science learning through the application of environmentally-based guided inquiry learning models in grade IV SDN INPRES Kabonena. This type of research is a classroom action research, using a spiral model design of Steven Mc. Taggart, which consists of 4 stages, namely planning, implementing, observing, and reflecting. The location of the research was at SDN INPRES Kabonena, Palu City. The research subjects were 20 students, consisting of 11 male students and 9 female students. The data consists of learning data including data on teacher skills and student activities. Data collection techniques are by observation and tests. Data analysis was performed by qualitative data analysis by concluding based on the mean value or standard deviation of observations (percentage of observations). The results showed that the students' ability in learning through the observation of teacher skills in the first cycle obtained a score of 22 with a good category percentage of 61%, and in the second cycle a score of 29 was obtained with a percentage of 81%, very good criteria. The ability of students in learning based on student activities in teaching and learning activities, in the first cycle a score of 21 was obtained, with a percentage of 58% in the sufficient category, and in the second cycle, it was obtained 27.5 with a percentage of 76.4% in the good category. Meanwhile, the student ability data obtained for pre-action, the number of students who completed as many as 5 students, with classical absorption (DSK) 50% and classical learning completeness (KBK) 25%. The data on student ability in the first cycle obtained 6 students with a DSK of 57% and a CBC of 30%, an increase in the second cycle where the number of students who completed 20 students with 88% DSK and 100% CBC While the data on student learning outcomes in the first cycle obtained 8 students with a DSK of 59% and a CBC of 40%, an increase in cycle II where the number of students who completed was 20 students, with a DSK of 87% and CBC 100%. Based on these results, it can be stated that the application of an environment-based guided inquiry learning model can improve problem-solving abilities and learning outcomes of fourth-grade students of SDN INPRES Kabonena.